Rasio Jenis Kelamin Kelahiran Anak Kambing Peranakan Ettawa (PE) Hasil Inseminasi Buatan Menggunakan Spermatozoa Swim Up - Sariadi Sariadi; Dasrul Dasrul; Muslim Akmal (Agricultural Faculty, 2014)
(The ratio of birth sex of ettawa crossbreed goat by artificial insemination using spermatozoa swim up)ABSTRACT. The aim of this research was to determine the ratio of birth sex of ettawa crossbreed goat by artificial insemination using spermatozoa swim up. This research was at Reproduction Laboratory Faculty of Veterinary medicine Syiah Kuala university and Livestock Group SMD, Bener Meriah Regency. Fifteen female goats with age 8-24 months where used in this study and divided into 3 treatment groups (P0, P1, P2) and 5 replications of each. The first group (P0) inseminated with sperm without swim up; P1 and P2 inseminated with sperm which swim up for 5 minutes (P1) and 10 minutes (P2). The result of conception rates observation and sex ratio of children born tabulated into tables. The data was analyzed by using analysis of variance (ANOVA) one way pattern followed by the multiple test Duncan. The results showed that the conception rate and birth sex ratio of male born had significantly different (P0,05). The segregation of sperm which swim up increased the conception rate and birth sex ratio of male born.